Discovering Unanticipated Dependency Schemas in Class Hierarchies - Arévalo, Gabriela Beatriz (^p Datos electrónicos (1 archivo : 191 KB))
Object-oriented applications are difficult to extend and maintain, due to the presence of implicit dependencies in the inheritance hierarchy. Although these dependencies often correspond to well-known schemas, such as hook and template methods, new unanticipated dependency schemas occur in practice, and can consequently be hard to recognize and detect. To tackle this problem, we have applied Concept Analysis to automatically detect recurring dependency schemas in class hierarchies used in object-oriented applications. In this paper we describe our mapping of OO dependencies to the formal framework of Concept Analysis, we apply our approach to a non-trivial case study, and we report on the kinds of dependencies that are uncovered with this technique. As a result, we show how the discovered dependency schemas correspond not only to good design practices, but also to "bad smells" in design. Keywords: Concept Analysis, Class Hierarchies, Schemas.